2021
DOI: 10.3389/fimmu.2021.704773
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Immunogenicity of the mRNA-BNT162b2 SARS-CoV-2 Vaccine in Hemodialysis Patients

Abstract: BackgroundHemodialysis patients are at high risk for severe COVID-19. SARS-CoV-2 vaccination related safety and immunogenicity data in these patients are rare.MethodsIn this observational study SARS-CoV-2-seronegative hemodialysis patients were vaccinated with two doses of the Pfizer/BioNTech mRNA-BNT162b2 vaccine (COMIRNATY® 30 µg) and followed for 90 days. Local and systemic side effects were assessed at every dialysis session during the first post-vaccination week after the first and second vaccine dose. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 37 publications
6
66
0
5
Order By: Relevance
“…We and others have found a high short-term seroconversion rate between 71% and 98% in hemodialysis patients following a complete two-dose vaccination course with the mRNA-BNT162b2 vaccine. 1 , 2 After natural infection 76% of hemodialysis patients remained seropositive after a median time period of 124 days after infection. 3 However, to our knowledge there are no serial data available on the maintenance of the vaccine-induced SARS-CoV-2 humoral response in hemodialysis patients.…”
mentioning
confidence: 99%
“…We and others have found a high short-term seroconversion rate between 71% and 98% in hemodialysis patients following a complete two-dose vaccination course with the mRNA-BNT162b2 vaccine. 1 , 2 After natural infection 76% of hemodialysis patients remained seropositive after a median time period of 124 days after infection. 3 However, to our knowledge there are no serial data available on the maintenance of the vaccine-induced SARS-CoV-2 humoral response in hemodialysis patients.…”
mentioning
confidence: 99%
“…A recent study confirmed the lack of antibody response in patients with X-linked agammaglobulinemia, compensated by the induction of an adaptive cellular response, whereas the response of patients with Common Variable Immunodeficiency was found to be unsatisfactory and non-protective at both cellular and humoral levels [ 100 ]. Safety and substantial immunogenicity were observed in patients with onco-hematological diseases [ 101 , 102 ] and in hemodialysis patients [ 103 ]. Despite the absence of comparative studies between mRNA and viral vector non-replicating vaccines, data from scientific studies and reports of regulatory authorities indicate better protection from mRNA vaccines.…”
Section: Safety Of Covid-19 Vaccines In Patients With Aiaids Pids and Sidsmentioning
confidence: 99%
“…This is a further consideration for prioritizing these patients in the access to vaccines to prevent the infection or, at least, a chronic infection. The Task Force does not consider it appropriate to interrupt/discontinue immunosuppressive therapy, excepting for high dosage CCS (≥10 mg of prednisone-equivalent [ 104 ]) and anti-CD20mAbs, such as rituximab [ 103 , 104 , 105 ] ( Table 3 ). Moreover, in the case of MTX [ 105 , 106 ], abatacept [ 105 , 106 ], JKI [ 105 , 106 ], and mycophenolate [ 106 ], the immunology specialist should evaluate the possible discontinuation based on the clinical patients’ characteristics.…”
Section: Should Patients With Aiaids Pids and Sids Be Prioritized In The Access To Vaccines?mentioning
confidence: 99%
See 2 more Smart Citations